173 THE EFFECT OF ALCOHOL ON LEVELS OF PHOSPHORYLATED CREB IN NEONATAL RAT HIPPOCAMPAL NEURONS. (1st January 2006) - Gilmore, J.; Schupbach, D.; Valenzuela, F.
Abstract : The spectrum of disorders associated with prenatal alcohol exposure is significant not only for the families directly affected but for society at large. Multiple mechanisms for the developmental abnormalities associated with these disorders have been proposed. An action of ethanol in the adult brain is to enhance GABAergic transmission, resulting in increased neuronal inhibition. It has recently been shown that ethanol has a similar effect on GABA activity in hippocampal slices from neonatal rats, although the result is neuronal excitation rather than inhibition. We hypothesized that this ethanol-induced excitation could increase levels of pCREB in neonatal neurons. To test this hypothesis, we measured pCREB and CREB levels by ELISA in extracts from control and ethanol-exposed hippocampal slices that were prepared from postnatal day 4-6 Sprague-Dawley rats. Contrary to our hypothesis, pCREB levels in the hippocampal tissue samples decreased in response to ethanol exposure compared to controls. CREB levels were also decreased in response to ethanol exposure and a pCREB:CREB ratio was calculated to determine if the decrease in pCREB paralleled the observed decrease in CREB. The calculations demonstrated an average 12-14% decrease in the ratio in response to ethanol exposure. The decreased levels of pCREB in response to ethanol exposure may be the result of activation of protein phosphatases by ethanol. Given the well-established role of pCREB in the development of neuronal circuits, we postulate that the alcohol-induced alterations in the levels of this transcription factor may contribute to the pathophysiology of fetal alcohol spectrum disorder.